THE DEVELOPMENT OF GOAT MILK KEFIR AND TOFU AT MENDHO SUBIREJO FARM KECAMATAN PURWODADI KABUPATEN PASURUAN - Abdul Manab (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2017)
The purpose of IbM program were the strengthen of technology adoption in milk coagulation, packaging and refrigeration at “Mendho Subi Rejo” farm to produce goat milk kefir and tofu thereby the production capacity were improved. “Mendho Subi Rejo” farm has produced and sold goat milk kefir and tofu with specific taste and texture. The application of coagulation technology, continue packaging and refrigeration at “Mendho Subi Rejo” farm improved the coagulation of goat milk tofu, the packaging of goat milk kefir and tofu, and stabilization goat milk produck during storage in refrigeration showcase. The application of these technology improved the production capacity of goat milk kefir and tofu